Potensi Prasasti Canggu Sebagai Sumber Belajar Sejarah Maritim Kerajaan Majapahit Kelas X SMA - Tyas, Novita Dwi Wahyuneng; Wahyudi , Deny Yudo (Jayapangus Press, 2024)
This research aims to determine and analyze the potential content of the Canggu Inscription to be used as an alternative learning resource for high school students, as well as to determine the opportunities and relevance of using the Canggu Inscription as a historical learning resource. In this research, the library research method was used. With the help of a content analysis approach, using the library study stages. In this writing, we utilize literature studies originating from several journal articles, books, official websites that are relevant and appropriate to the topic discussed. This study will also provide alternative additional material related to the Canggu Inscription, including a description of the contents of the Canggu Inscription, life in government, economics, religion, as well as patterns of diplomatic relations and trade bureaucracy that occurred at that time, which is linked to the content of learning outcomes so that it will can be used as an alternative learning resource for students, especially at class X high school level.